(untitled) (diségno, 2019)
The University of Trieste hosted, from 24 to 28 September 2018 at the Gorizia University Pole, the first PhD Summer School of the Unione Italiana per il Disegno on survey of cultural heritage and inclusive representation dedicated to advanced doctoral training in the disciplines of representation [1]. The Summer School introduced participants to the practice of the most advanced tools and methodologies for the analysis, documentation and communication of cultural heritage. In addition, the participants were able to apply digital representation workflows in the field of scientific knowledge and dissemination, with particular attention to accessibility of collections and their effective and universal fruition